(untitled) (Development Service Industry Management, 2023)
The article examines the essence of the concept of "conflict" and determines that there are the following approaches to its understanding: destruction of relations / struggle; a situation of confrontation / confrontation; a means of resolving contradictions; collision of multidirectional forces; relationship status. The author’s definition of the concept of "conflict" is given, in particular, conflicts should be understood as a situation where there is a clash of interests of two or more sides with conflicting goals, interests, needs, values, beliefs, etc. Different situations can lead to conflicts, including differences in values and beliefs, the competition for resources, the incompatibility of tempers and characters, stressful situations, incompatibility in work styles, ambition, cultural and ethnic disparities, differences in ideas and objectives, and so on. Conflict can arise in any sphere of life - from personal to international relations, and have various forms of manifestation, ranging from misunderstandings to open conflicts. The importance of conflict management in enterprises lies in ensuring productivity and harmonious cooperation among employees, while balancing the interests of all groups. In addition, conflict management depends on the stages, which include conflict detection (the first stage), in particular, it is necessary to recognize the presence of a conflict in the enterprise, which is realized by detecting tension in the relationship at the enterprise, a decrease in productivity or a deterioration of communication between employees. The second stage is the study of the causes of the conflict, in particular, it can be a difference in ideas, competition, misunderstanding, etc. The third stage is planning of a conflict resolution strategy, that is, the development of an action plan to resolve the conflict, and may include various ways to reduce tension, find a compromise, or implement new policies and procedures. The fourth stage is the implementation of the conflict management strategy, which involves developing of an action plan to resolve the conflict. In the fifth stage, results are evaluated and reviewed. If the conflict was successfully resolved, it is worth to analyze what exactly brought success, and if it was not possible to achieve success, it is worth to understand the reasons, to make an adjustment to the strategy. The sixth stage is the creation of preventive measures to avoid similar conflict situations in the future.